Sufism As Therapy Psychological Problems of Modern Society - Al Halim , Adibudin; Suwito; Nawawi; Wan Mohammed, Nik Kamal (Advances in Humanities and Contemporary Studies, 2024)
Modernity gave rise to many advances as well as problems for modern society, including psychological problems. They tend to pursue material life and have a materialistic lifestyle rather than thinking about religion, which is considered to play less of a role in living life. One of the factors that can trigger negative impacts is a materialistic, hedonistic attitude to life, and the desire to control all aspects of life excessively and blindly. General symptoms of unhealthy mental health can be seen from several aspects, namely feelings of anxiety, feeling disturbed, unreasonable fear, envy, arrogance, negative behavior. These diseases arise because the heart is not calm, because the heart is far from God. Sufism is present in society as a solution to overcome and anticipate human psychological problems. Therefore, this researcher attempts to carry out an analysis of the teachings of Sufism as a therapy for human problems from a psychological perspective. This research method is a type of qualitative research based on library literature data, with a deductive-inductive thinking pattern. In this research, the primary sources consist of literature that is directly related to the research variables, namely various data regarding Islamic psychology and Sufism. Meanwhile, the secondary source is data related to this research. The research approach uses a psychological approach. For this reason, the author tries to conclude that psychology and Sufism can be interpreted as a science that discusses the human psyche and has the same role, namely providing solutions and overcoming human problems in living life. Modern humans are humans who think logically and are able to use various technologies to improve the quality of their personal and social lives. However, the result of this imbalance can then cause mental disorders.